ANALISIS RULE INFERENSI SUGENO DALAM SISTEM PENDUKUNG PENGAMBILAN KEPUTUSAN - Khairul Saleh (Universitas Methodist Indonesia, 2016)
The issue of decision-making, is essentially a form of selection of various alternative actions that may be selected which process a particular mechanism, with the hope of producing a best decision. Fuzzy logic can be used to describe a chaotic dynamic system, and fuzzy logic can be useful for systems that are complex dynamic in which the completion of the general mathematical model that can not work properly. Sugeno fuzzy method to compute efficiently and work well with the optimization and adaptive techniques, which makes it very well in a control problem, especially for non-linear dynamic systems.